Armenia through the Lens of Time Multidisciplinary Studies in Honour of Theo Maarten van Lint - Alpi, Federico; Meyer, Robin; Tinti, Irene; Zakarian, David (Brill, 2023)
The open access publication of this book has been published with the support of the Swiss National Science Foundation. From pilgrimage sites in the far west of Europe to the Persian court; from mystic visions to a gruesome contemporary "dance"; from a mundane poem on wine to staggering religious art: thus far in space and time extends the world of the Armenians. A glimpse of the vast and still largely unexplored threads that connect it to the wider world is offered by the papers assembled here in homage to one of the most versatile contemporary armenologists, Theo Maarten van Lint. This collection offers original insights through a multifaceted lens, showing how much Armenology can offer to Art History, History, Linguistics, Philology, Literature, and Religious Studies. Scholars will find new inspirations and connections, while the general reader will open a window to a world that is just as wide as it is often unseen.